Dynamic Analysis of the Modified Leslie Gower Model with Harvesting of Prey and Holling Type II Functional Response - Eghary, Nabila Kholifatul Yuniar; Savitri, Dian (Gammarise Publishing, 2025)
This article studies the Modified Leslie-Gower model with constant business harvesting on the prey and functional response of Holling Type II. This approach is more realistic in several phenomena, one of which is in the phenomenon of rice fields, jali snakes, and owls. The research method begins by determining the assumptions for constructing models, stability analysis, and numerical simulations. Analysis of the equilibrium points was carried out to determine the condition of its stability locally using the Jacobian approach and the Routh-Hurwitz criteria by obtaining five existing points. Analysis of stability using the Jacobian matrix shows that the equilibrium point is an asymptotic node in certain conditions. Numerical simulations are carried out to determine the suitability of the results of the analysis using the software Maple and Python. Numerical simulation results show differences in the value of environmental carrying capacity affect changes in system solutions. Thus, the change in the value of carrying capacity does not always produce the same stability because the stability of the system depends on the sensitivity of the parameter to the overall dynamic structure. This finding provides a foundation for the management of biological resources, especially in controlling harvesting so that the population remains balanced.